An Assessment of Fire Hazard in the Historic Town of Ouro Preto based on Four Established Analysis Methodologies (Global Journal of Human-Social Science, 2022)
Abstract not found
Keywords: risk assessment methodology – fire risk management – historical sites –vulnerability – resilience – mitigation actions